Psychological Distress and Tobacco Use Among Hospital Workers During COVID-19 - Mounir, Izza; Menvielle, Loick; Perlaza, Samir; Chênevert, Denis; Planchard, Jo-Hanna; Fabre, Roxane; Benoit, Michel; Benyamina, Amine; Rolland, Benjamin; Cherikh, Faredj; David, Renaud (Frontiers in Psychiatry, 2021)
Background and Aims: This work aims to assess the impact of the COVID-19 pandemic on hospital workers' psychological parameters and attitudes toward substance use, before and during the French COVID-19 lockdown. Methods: An online survey was proposed to the staff of the University Hospital of Nice and Sainte-Marie psychiatric hospital in France from May 18 to June 6, 2020 assessing changes in daily habits, psychological distress and changes in substance use, including smoking. Results: A total of 702 respondents (80.3% female) filled out the survey. Overall, most of the workers reported increased stress, irritability, sadness, decreased motivation, and a worse quality of sleep after the beginning of the COVID-19 lockdown. Additionally, hospital workers who were more likely to use tobacco during the COVID-19 lockdown reported increased sadness (OR = 1.23, p < 0.001), loss of motivation (OR = 0.86, p < 0.05), alcohol consumption (OR = 3.12, p < 0.001), lower incomes (OR = 1.69, p < 0.05), living alone (OR = 1.77, p < 0.001) and doing less physical activity (OR = 0.36, p < 0.001). Conclusion: During the first lockdown, significant psychological changes (sadness, distress, irritability) associated with changes in tobacco use and physical activity were reported. Such results should encourage hospital leaders to implement dedicated policies to better accompany hospital workers' psychological distress.